Making all things new : God's dream for global justice - Moore, R. York, 1969- (Downers Grove, Ill. : IVP Books, 2012)
God has a dream. York Moore paints a vivid picture of how the dream of God is breaking into history to make all things new. Through the death and resurrection of Jesus, God is bringing an end to the world's nightmare of sin and death. Scripture's vision of Jesus' end-time work shows how the wrongs will be made right, and God's just judgment is good news for the world. Unpacking how the Bible describes the last things, Moore shows how we can partner with God as he brings his dream to reality. Every time a well is dug for a community, food is provided for the hungry or sex traffickers are brought to justice, the dream begins to take hold. --Amazon.com
Dreams of another world -- Between two dreams -- Power in the blood -- The end-time work of Christ -- A war-waging Jesus -- A global invitation of joy -- The wedding of all time -- A distant thunder -- The end of our dream -- Fire in the sky -- God's great city -- The dream of God and mission -- A dream beyond justice -- Joining God in making all things new.
Includes bibliographical references.
Description based on print version record.
Keywords: Social justice -- Religious aspects -- Christianity; Christianity and justice; Social change -- Religious aspects -- Christianity; Church and social problems; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books